Coal permeability considering mining-induced stresses subjected to fractional derivative. (December 2022) - Zhou, Hongwei; Xie, Senlin; Jia, Wenhao; Zhao, Jiawei; Sun, Xiaotong; Yang, Shuai; Wei, Qing; Wang, Xiangyu
Abstract: Aiming at characterization of coal permeability under conditions of non-Darcian flow, in the transient pulse test, a new fractional-order decay model is developed to describe the pressure difference decay of coal considering mining-induced stresses. Coal permeability under the condition of mining-induced stress is determined experimentally by the MTS815 Flex Test GT testing machine to validate the fractional-order decay model. The results indicate that the new fractional-order decay model can estimate the permeability of coal considering mining-induced stresses more accurately than the exponential decay model. A conceptual permeability model of coal considering mining-induced stresses is obtained by characterization analysis of coal permeability evolution. Furthermore, the meaning of the fractional order is discussed, showing that it can be used to characterize the influence of mining-induced stresses on the seepage characteristics of coal. Highlights: A new fractional-order decay model of coal is developed. The experiments are carried out to verify the fractional-order decay model. The meaning of fractional order in the fractional-order decay model is discussed.